Renal vein thrombosis in nephrotic syndrome–a prospective study and review. Issue 671 (September 1981) - Chugh, K. S.; Malik, N.; Uberoi, H. S.; Gupta, V. K.; Aggarwal, M. L.; Singhal, P. C.; Suri, S.; Jain, S. K.
Abstract : The incidence of renal vein thrombosis (RVT) and other thrombo-embolic phenomena was evaluated in 44 unselected patients with nephrotic syndrome. Renal vein thrombosis was demonstrated by selective renal venography in 10 patients and at post-mortem in one. Extension of the thrombus from the renal veins into the inferior vena cava was seen in 3 patients. Evidence of thrombo-embolism elsewhere in the body was seen in the form of thrombophlebitis in the lower extremities in 4 patients (9.1%), pulmonary embolism in 3 (6.8%) and myocardial infarction in one (2.3%). Of the 11 patients with RVT, renal histology showed membranous glomerulonephritis in 3, minimal change nephritis in 5, membrano-proliferative in one and focal and diffuse proliferative glomerulonephritis in one patient each. The characteristics clinical findings such as gross haematuria and flank pain were noted in only 3 patients with RVT. No significant difference could be detected between the plasma fibrinogen, serum cholesterol, beta-lipoprotein, triglycerides and phospholipid concentration of those who showed RVT and the remainder in whom RVT was not demonstrated. The possible mechanisms involved in the pathogenesis of RVT in nephrotic syndrome are discussed.